Fiqh al-Tasamuh dalam Hukum Perdata Islam: Mewujudkan Moderasi dalam Relasi Sosial dan Keluarga di Era Kontemporer - Mohsi Mohsi (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2025)
The contemporary era is marked by rapid social change, digitalized relationships, and increasingly complex interactions within both society and families. In this context, Fiqh al-Tasamuh (Islamic jurisprudence of tolerance) offers a relevant normative framework for fostering inclusive, just, and harmonious social and familial life. Core values such as tawassuth (moderation), i’tidal (balance), tawazun (proportionality), and tasamuh (tolerance) have proven effective in addressing modern challenges—ranging from social media use within households and strengthening interfaith relationships to reforming family law based on the objectives of Islamic law (maqāṣid al-sharī‘ah). Recent studies indicate that this moderate approach not only reduces domestic conflicts but also promotes social coexistence amid diverse identities. Despite resistance from conservative groups and digital polarization, fiqh al-tasamuh presents a contextual and progressive ethical-legal response. By enhancing moderate religious literacy, fostering collaboration between religious figures and the state, and integrating tasamuh values in family education, societies can cultivate a more peaceful and equitable civilization. Thus, fiqh al-tasamuh is not merely a theoretical discourse but a practical tool for navigating the moral and legal complexities of the modern world.